Transdermal delivery of CRISPR/Cas9-mediated melanoma gene therapy via polyamines-modified thermosensitive hydrogels - Meng Li; Songli Zhou; Suqin Zhang; Xingyu Xie; Junqi Nie; Qi Wang; Lixin Ma; Yibin Cheng; Jingwen Luo (Journal of Nanobiotechnology)
Abstract The main obstacles to the clinical application of the CRISPR/Cas9 system are off-target effects and low delivery efficiency. There is an urgent need to develop new delivery strategies and technologies. Three types of in situ injectable hydrogels with different electrical properties were created to find the most secure and efficient sustained-release drug delivery system. After in vitro and in vivo comparisons, we found that the positively charged hydrogels had higher cellular uptake, stronger gene editing efficiency, greater cytotoxicity, longer tumor accumulation, and better anti-tumor efficacy than negatively charged and neutral hydrogels. We designed single guide RNA targeting the Y-box binding protein 1 (YB-1) gene and then used it to create a ribonucleoprotein complex with Cas9 protein. Doxorubicin was co-encapsulated into this positively charged hydrogel to create a co-delivery system. By knocking down YB-1, the expression of YB-1 was reduced, inhibiting the growth and migration of melanoma cells. The strategy of combining YB-1 gene editing and intratumoral injection enhanced the therapeutic effect of doxorubicin while reducing side effects.